Edutaining with indigeneity: Mediatizing Ainu bilingualism in the Japanese anime, Golden Kamuy. (November 2022) - Ito, Rika
Abstract: This article examines how the Ainu language, a critically endangered indigenous language of northern Japan, is deployed in the Japanese animation Golden Kamuy (Noda, 2018-). The Ainu language is mediatized as loanwords and the language of the community primarily in Ainu–Japanese interactions. The Ainu co-protagonist's skillful translation of loanwords makes Ainu culture accessible to the viewers. Such considerate representations reflect the creator's extensive research and commitment to overcoming discrimination against Ainu. Unfortunately, however, careful analysis of overall Ainu language allocational patterns reveals that the show cannot escape from reproducing race-related discourses in Japan, reflecting Japan's colonial legacy. Highlights: Analyzes how the Ainu, a critically endangered language, is mediatized in anime . Incorporates notions of a raciolinguistic perspective and edutainment in analysis. Finds mediatized bilingualism as loanwords and the language of the community. Identifies that loanwords function to teach many aspects of Ainu's unique culture. But also finds that other Ainu deployment reproduces race-related discourses.